The impact of U.S. monetary policy on foreign firms - Julian Di Giovanni; John H. Rogers (Federal Reserve Bank of New York, 2022)
This paper uses cross-country firm-level data to explore the impact of U.S. monetary policy shocks on firms' sales, investment, and employment. We estimate a sizeable impact of U.S. monetary policy on the average foreign firm, while controlling for other macroeconomic and financial variables like the VIX and exchange rate fluctuations that accompany U.S. monetary policy changes. We then quantify the role of international trade exposure and financial constraints in transmitting monetary policy shocks to firms, allowing for a better identification of the importance of external demand effects and the interest rate channel. We first exploit cross-country sector-level data on intermediate and final goods' data to show that greater global production linkages amplify the impact of U.S. monetary policy at the firm level. We then show that the impact varies along the firm-level distribution of proxies for firms' financial constraints (for example, size and net worth), with the impact being significantly attenuated for less constrained firms.
Keywords: E52; F40; 330; U.S. monetary policy spillovers; foreign firms; international production linkages; financial constraints